Use of a hypercaloric and hyperprotein supplement enriched with immunonutrients in multi-pathological malnourished patients to improve the incidence and prevalence of pressure sores: A randomized controlled trial - Eduardo Sánchez-Sánchez; Jara Díaz-Jiménez; Alejandro García-García; Alejandro Úbeda-Iglesias; Borja Muñoz-Tejada; Javier Martínez-Diegues; Cristina Sánchez-Fernández; Marina Erola-Moreno; Borja Vallecillo-Rico; Cristina Jiménez-Vázquez; Blanca Bohorquez-Almagro; Sol-Paula Cortés de Miguel; et al. (PLoS ONE, 2026)
Background Predisposing factors for the development of pressure-related injuries (PRIs) include the presence of chronic diseases, polypharmacy, immobility and malnutrition. Nutrients such as arginine play an essential role in wound healing. Methods and findings A single-blind randomized controlled trial was carried out. Intervention group received a complete hyperproteic and hypercaloric oral nutritional supplement with a fiber mixture enriched in omega 3, L-arginine and nucleotides, providing vitamin C and Zinc, and the control group received a hyperproteic and hypercaloric oral nutritional supplement with fiber mixture. Results Descriptive analysis indicated a lower frequency of PRIs at 15 and 30 days in the Atémpero ® group compared to the control group, although these differences did not reach statistical significance. However, both improved at the end of the study. In addition, the high risk decreased in both groups, with a higher decrease in the Atémpero ® group (72.5% vs 40.9%), as well as the categorization and parameters of the PUSH scale, with a reduction of the same in the Atémpero ® group. Conclusions While statistical significance was not achieved, the observed trends in PUSH scale scores and clinical observations within the Atémpero ® group suggest areas for further investigation. These preliminary data highlight a potential avenue for the nutritional management of multi-pathological patients, establishing a solid foundation for future large-scale confirmatory trials to validate the efficacy of immunonutrient-enriched ONS in pressure injury care. Trial registration. ClinicalTrials.gov NCT06726486 .